PENGARUH MINAT MENJADI GURU TERHADAP HASIL BELAJAR MAHASISWA PADA PROGRAM STUDI PENDIDIKAN AKUNTANSI ANGKATAN TAHUN 2014 DAN 2015 UNIVERSITAS GUNUNG RINJANI (UGR) - MURAH; admin admin (LPPM Universitas Gunung Rinjani, 2019)
The purpose of this study is to determine the influence of Interest Being Teachers onStudents Learning Outcomes In Accounting Education Studies Program Force Year 2014 and 2015 University of Mount Rinjani (UGR). The type of research used in this study is ex-post facto. According to Sukardi (2013: 165), ex-post facto research is a study in which free variables have occurred or existed before and can not be manipulated when the observationof the dependent variable is initiated. While the method used is quantitative descriptivemethod which means research trying to describe a phenomenon of events and events at thepresent time and reveal data that has been going without manipulating other variableswithout affecting the dependent variable. Based on the results of the study can be knownaverage student learning outcomes of accounting education courses both teacher trainingprograms and accountability skill both average. While students who are interested inbecoming a bigger teacher than students who are not interested in becoming a teacher. Fromthe results of hypothesis testing, it turns out Ho is rejected first tested with prerequisite test sothat it can be continued to diregresi.Ini means the interest to be a teacher significantlyinfluence the student learning outcomes.